Pengetahuan dan Sikap mengenai Infertilitas pada Mahasiswa Fakultas Kedokteran dan Fakultas Non Kedokteran Universitas YARSI - Annisha Jehan Khaerunnisa; Mirfat Mirfat (Lembaga Penelitian Universitas YARSI, 2019)
Infertility is a disease characterized by the failure to establish a pregnancy after 12 months of regular unprotected sexual intercourse. As the incidence of infertility increases, knowledge and attitude about infertility on students may decrease the incidence of infertility in the future. The aim of this study is to determine and compare the knowledge and attitude regarding infertility among YARSI University students based on their faculty and gender. This was an analytic study with cross-sectional design, which conducted on September until November 2016. The samples were using bachelor’s degree students from 2013 classes of YARSI University in total 86 respondents. Data were obtained by using questionnaire that has been validated. This study used univariate and bivariate analysis method.The results of this study showed that majority of students have moderate level of knowledge regarding infertility (46,5%) and good attitude towards infertility (97%). Significant difference was found in knowledge about infertility between faculties (p value 0,000; less than 0,05). While there was no significant difference in knowledge about infertility between genders with (p value 0,471; more than 0,05). Significant differences were also not found in attitudes regarding infertility between faculties with (p value 0,399; more than 0.05) and genders with (p value 0,083; more than 0.05). Based on the research results medical students have a better knowledge about infertility than non-medical student. Faculty affect the knowledge about infertility, but do not affect the attitude towards infertility. Meanwhile, genders do not affect both knowledge and attitude towards infertility. Thus, it is important to improve student’s knowledge and attitude regarding infertility